JUÇARA SEEDLING PRODUCTION WITH AGROINDUSTRY WASTES AND COMPOSTED SEWAGE SLUDGE - De Melo Silva, F. A.; De Souza, I. V.; Zanon, J. A.; Nunes, G. M.; Da Silva, R. B.; Ferrari, S. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The present work evaluated the use of organic compounds produced from agroindustry residues of palm heart and sewage sludge with different levels of fertilizer as a substrate for production juçara seedlings (Euterpe edulis Martius). The experimental design was a 3x4 entirely randomized factorial scheme. The treatments were sewage sludge based substrates and palm hearth agroindustry waste (three levels: biosolid + palm hearth in 1:1, 1:2 and 1:3 volume proportions) and granular fertilizer doses (four levels: 0, 2.0, 4.0 and 6.0 g dm-3), with four replications, being used as useful plot the amount of ten plants. A commercial substrate was used as additional treatment The measured variables were: stem diameter, plant height, plant height/stem diameter, shoot dry weight, root dry weight, Dickson's Quality Index, nutrients in the shoot and quality of the root ball. The use of biosolids and palm hearth as substrate was viable in the production of juçara seedlings. The tested substrates may be used for the production of juçara seedlings without the addition of granulated fertilizer.